(untitled) (Globalization and Business, 2018)
In accordance with the theory of demographic transition, the following article analyzes peculiarities of Georgia’s demographic modernization during XIX-XX centuries and at modern stage. Peculiarities of the impact of global and local political and social-economic factors on the modernization of demographic system are discussed according to the separate stages and the intertype period of the modern type of population reproduction.